1997
DOI: 10.1083/jcb.137.3.595
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sorting of Lysosomal Enzymes Out of the Regulated Secretory Pathway in Pancreatic β-Cells

Abstract: In cells specialized for secretory granule exocytosis, lysosomal hydrolases may enter the regulated secretory pathway. Using mouse pancreatic islets and the INS-1 β-cell line as models, we have compared the itineraries of procathepsins L and B, two closely related members of the papain superfamily known to exhibit low and high affinity for mannose-6-phosphate receptors (MPRs), respectively. Interestingly, shortly after pulse labeling INS cells, a substantial fraction of both proenzymes exhibit regulated exocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(155 citation statements)
references
References 98 publications
8
146
1
Order By: Relevance
“…In chromaffin cells, the high degree of colocalization of cathepsin L immunofluorescence with ME, confirmed by dual immunoelectron microscopy, demonstrates trafficking of cathepsin L to the regulated secretory pathway. In fact, earlier studies have indicated that cathepsin L is routed to immature secretory granules of insulinproducing cells, and a significant portion of cathepsin L remains as a resident protein of the mature secretory vesicle (26). In addition, cathepsin L is present in secretory granules of pituitary GH4Cl cells and undergoes regulated secretion induced by the secretagogues forskolin and phorbol 12-myristate 13-acetate (27).…”
Section: Figmentioning
confidence: 99%
“…In chromaffin cells, the high degree of colocalization of cathepsin L immunofluorescence with ME, confirmed by dual immunoelectron microscopy, demonstrates trafficking of cathepsin L to the regulated secretory pathway. In fact, earlier studies have indicated that cathepsin L is routed to immature secretory granules of insulinproducing cells, and a significant portion of cathepsin L remains as a resident protein of the mature secretory vesicle (26). In addition, cathepsin L is present in secretory granules of pituitary GH4Cl cells and undergoes regulated secretion induced by the secretagogues forskolin and phorbol 12-myristate 13-acetate (27).…”
Section: Figmentioning
confidence: 99%
“…Occasionally, ICA69 was detected on what appeared to be small vesicles pinching off the membrane of SGs. Whereas the presence of a coat was not readily apparent, such profiles could conceivably represent budding clathrin-coated vesicles that remove proteins not destined to MSGs (57,67,68). Protein removal from ISGs is part of the maturation process that leads to the formation of MSGs (69,70).…”
Section: Enrichment Of Ica69 On the Golgi Complex By Subcellularmentioning
confidence: 99%
“…Because this result was not expected, we considered at the time the alternative that a portion of dense granule proteins was released via a budding process from forming dense granules, analogous to the situation in pancreatic ␤-cells (27). Failure to block dense granule protein release using Brefeldin A was interpreted at the time to provide evidence that all release was from preformed dense granules.…”
Section: Augmented Dense Granule Protein Release With Gtp␥s Reflects mentioning
confidence: 99%